Computer-Assisted Virtual Planning for Surgical Guide Manufacturing and Internal Distractor Adaptation in the Management of Midface Hypoplasia in Cleft Patients. (July 2017) - Scolozzi, Paolo; Herzog, Georges
We are reporting the treatment of severe maxillary hypoplasia in two patients with unilateral cleft lip and palate by using a specific approach combining the Le Fort I distraction osteogenesis technique coupled with computer-aided design/computer-aided manufacturing customized surgical guides and internal distractors based on virtual computational planning. This technology allows for the transfer of the virtual planned reconstruction to the operating room by using custom patient-specific implants, surgical splints, surgical cutting guides, and surgical guides to plate or distractor adaptation.